Virtualized Violence and Anonymous Juries: Unpacking Steubenville's "Big Red" Sexual Assault Case and the Role of Social Media. (December 2018) - Fairbairn, Jordan; Spencer, Dale
In this article, we analyze a 2012 sexual assault case from Steubenville, Ohio, and the hacktivist "Anonymous" group response to the sexual assault. Drawing on Paul Virilio's discussion of dromoscopy and concept of virtualization, we demonstrate the speed at which a "local" sexual assault can be exposed and go viral and how broader publics can be interpellated as bystanders in such cases. We show how emerging forms of online activism are exposing and contesting these new forms of violence against women and consider their potential to erode criminal justice blockages to justice for survivors of sexual violence.